Immunization in India : An Equity-Adjusted Assessment - Gaudin, Sylvestre; Yazbeck, Abdo S. (World Bank, Washington, DC, 2013)
An analysis of the 1992-93 National Family and Health Survey (NFHS) revealed wide differences in levels, and distribution of childhood immunization between, and within Indian states. Evidence of total system failure (no immunization for all) in some low performance areas suggested that improvements in immunization levels may come with a worsening of the distribution of immunization based on wealth. Using the latest NFHS data (1998-99), we take a new snapshot of the situation and compare it to 1992-93, focusing on heterogeneities between states, rural-urban differentials, gender differentials, and more specifically on wealth-related inequalities. In order to assess whether improvements in levels were accompanied by distributional improvements (or whether inequalities were reduced at the expense of overall achievement), we use recently developed methodology to calculate an extended achievement index that captures performance both in terms of efficiency (change in overall immunization rates) and equity (distribution by wealth quintiles) for each of the seventeen largest states. Comparing 1992-93 to 1998-99 levels using different degrees of "inequality aversion" provides no evidence that distributional improvements come at the expense of overall performance.